THE PREVALENCE OF DENTOALVEOLAR ANOMALIES AND DEFORMITIES IN PATIENTS WITH DENTAL DEFECTS. - B.M. Mirchuk; Y.V. Maksymov (Ukrainian Medical Stomatological Academy, 2018)
As result of the presence of defects in the dentition, a range of morphological, aesthetic and functional changes arises, which considerably complicates the process of diagnosis and treatment of this pathology. Defects in the dentition, in combination with a variety of anomalies and deformations, often impede the implementation of rational prosthetics, and occasionally make it, impracticable at all one to this reason, one of the urgent problems in modern dentistry, which requires further, is the study of adverse factors that arise in the prosthetics of dental defects in adult patients with dentoalveolar anomalies and deformations of different etiologies. The aim is to investigate the prevalence of dental anomalies and deformities in adult patients' prosthetic treatment. Materials and methods. 83 patients aged 20-60 and older were involved in prosthetic treatment. The diagnosis was based on classification have been of surveyed on Kennedy and D.A. Calveliss. Patients were divided into 4 age groups: Group I included 49 patients aged 20 to 30 years; Group II included 10 patients aged 31 to 40 years; Group III included 13 patients aged 41 to 50 years; IV group contained 11 patients aged 51 to 60 years and older. Results. In the 1st group, with coverage of 49 persons aged 20 to 30 years 12,5% of women suffered from defects of dentition which was under half the size of that of men (29,4%).All patients with dental defects needed prosthetic treatment. The prevailing majority of the surveyed-96,9% of females and 100% of males were diagnosed with dental anomalies. In group II, with 10 patients being examined in the 31-40 aged bracket, a significant increase in the number of persons with dental defects was observed: in women by 5.7 times up to 71,4% and in men-by 2.7 times up to 66,7% in comparing with those in Group I. Each of the examined patients with dental defects needed protection and orthodontic treatment. All patients in the third group (41-50 years) and the in IV group ( 51-60 years and older) of defects of dentitions were 50.0% women and 57.1% men of the third group and 71,4% of women and 75,0% of men of the IV group needed prosthetics of secondary dentition of teeth. Al l women of both subgroups have been diagnosed with dental anomalies, whereas in men. Orthodontic pathology was detected in 85,7% of individuals of group III and 75,0% of individuals group IV. Conclusions. Prosthetic treatment with restoration of the integrity of the dentition is one of the reasons for the significant growth of secondary deformations and the formation of dentoalveolar anomalies. According to our observations, patients 30 years of age or older who seek orthopedic help have defects in the dentition. Most often, these patients are diagnosed with included dentition defects in the lateral areas (from 35.3% to 63.6%), which are complicated by secondary deformations of the dentition (from 33.3% to 100%). The results of the studies confirm the need for further study of the state of the dentoalveolar system in patients with dentition defects, namely: the formation of secondary deformations, occlusion disorders, changes in the shape and size of the dentition, decrease in occlusion height, temporomandibular joint dysfunction, blockage or forced mandibular position etc.